Knowledge and attitude toward organ donation among people in Lanja: A rural town in India - Vaishaly K Bharambe; Vasanti U Arole; Vatsalaswamy Puranam; Preeti P Kulkarni; Prashant B Kulkarni (Saudi Journal of Kidney Diseases and Transplantation, 2018)
Organ shortage is the greatest challenge facing the field of organ transplantation today. We aimed to study the attitude and knowledge toward body and organ donation among people in rural India. The present study was conducted in a rural town called Lanja, in the Konkan region of Maharashtra in India. A questionnaire covering demographic data, knowledge, and attitude of the participants was distributed to 400 students, middle-aged and senior citizens; 91.5% of the respondents were aware about organ donation. Television (55.2%) and newspaper (45.8%) were the most popular sources of information. About 56.2% and 32.8% believed that a healthy person and a cardiac dead person can be donors, respectively. Nearly 29.4% believed that a brain-dead person can be a donor and 22.4% clearly stated as to be having no idea regarding the health status of a donor. Highest awareness was observed regarding eye donation (92%). High awareness was also observed regarding heart, kidney, and liver donations, that is, 71.1%, 61.2%, and 54.2%, respectively. Awareness regarding donation of other tissues and organs was poor. Only 46.8% believed that the family of the deceased person can give consent for organ donation if the donor had not signed the donor card. Awareness regarding both body and organ donation in rural India is high. However, there is lack of understanding regarding the concept of brain-death. Awareness regarding body and other organ and tissue donations besides eye, kidney, etc., needs further awareness drives.